Assessment of patient perspectives in the CONVINCE trial in end-stage kidney disease - a domain-guided approach - Kathrin I. Fischer; Krister Cromm; Peter J. Blankestijn; Bernard Canaud; Jörgen Hegbrant; Claudia Barth; Mark Woodward; Giovanni F. M. Strippoli; Andrew Davenport; Michiel L. Bots; Matthias Rose (Frontiers in Nephrology, 2026)
Background Patient-reported outcome (PRO) measures are increasingly used in clinical trials and clinical care to assess symptoms, functioning, and health-related quality of life (HRQoL). In dialysis research, instrument-driven approaches that rely on legacy measures may not fully capture outcomes that matter most to patients or treatment-related experiences such as dialysis-specific fatigue and recovery. Therefore, a patient-informed, domain-guided PRO toolbox for adults with end-stage kidney disease (ESKD) receiving maintenance dialysis was developed and applied in the CONVINCE trial. Methods A multi-method, triangulation approach was used, comprising: 1) a targeted literature review of PROMs and symptom concepts used in maintenance dialysis research, 2) review of international core outcome initiatives relevant to kidney disease and haemodialysis, 3) semi-structured interviews and focus groups with patients ( n = 13) and health care professionals ( n = 4). Concepts identified across sources were compiled, compared, and prioritized based on recurrence across evidence sources, salience to patients, anticipated sensitivity to dialysis modality, and feasibility of repeated assessment within the CONVINCE trial. Results The literature review identified 97 PROMs. Domains and symptom content were extracted from these instruments and mapped against concepts covered by international core outcome initiatives and qualitative data. Triangulation resulted in an ESKD PRO toolbox comprising nine prioritized health domains: general health/health perception, fatigue, physical function, social roles, depression, anxiety, pain, sleep, and cognitive function. Most of these domains could be assessed within the PROMIS ® health domain framework. To complement these generic domain measures, a dialysis-specific symptom list and additional items to assess dialysis-related fatigue, treatment-related recovery time were included. Conclusion The ESKD PRO toolbox provides a patient-informed, domain-guided framework for repeated longitudinal assessment of outcomes relevant to patients receiving maintenance dialysis. Its application in CONVINCE illustrates how PROMIS ® -based domain assessment can be combined with dialysis-specific symptom and fatigue measures to capture treatment-related patient experiences.